If the function is odd, then it is symmetric about the origin, i.e. .
Any function of the form:
where are constants and and are not both zero
is an odd function, since:
Hi all,
Can someone please help me understand how the following function is symmetric about the origin?
y = 3x /(x^2 + 9)
-y = 3(-x) / (-x)^2 + 9
-y = -3x / x^2 + 9 (multiply numerator and denominator by -1)
y = 3x/ -x^2 -9
The functions are not the same yet, in the back of my book it says that it is symmetric about the origin.
Thanks for the help,
Alex